2022
DOI: 10.3389/fpls.2022.1009630
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of chlorophyll content under the stress of leaf mite for jujube based on model PSO-ELM method

Abstract: During the growth season, jujube trees are susceptible to infestation by the leaf mite, which reduces the fruit quality and productivity. Traditional monitoring techniques for mites are time-consuming, difficult, subjective, and result in a time lag. In this study, the method based on a particle swarm optimization (PSO) algorithm extreme learning machine for estimation of leaf chlorophyll content (SPAD) under leaf mite infestation in jujube was proposed. Initially, image data and SPAD values for jujube orchard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…The same trend followed in our study; the healthy plants showed higher reflectance radiation in NIR region than the BPH-infected plants. The Previous study of Lu et al (2022) also revealed similar spectral signature for leaf mite infestation in the crop jujube. A similar trend was pursued in the earlier study of Riedell and Blackmer (1999) observed in wheat seedlings with aphids (Diuraphis noxia) and greenbugs (Schizaphis graminum).…”
Section: Spatial Signature Of N Lugenssupporting
confidence: 57%
“…The same trend followed in our study; the healthy plants showed higher reflectance radiation in NIR region than the BPH-infected plants. The Previous study of Lu et al (2022) also revealed similar spectral signature for leaf mite infestation in the crop jujube. A similar trend was pursued in the earlier study of Riedell and Blackmer (1999) observed in wheat seedlings with aphids (Diuraphis noxia) and greenbugs (Schizaphis graminum).…”
Section: Spatial Signature Of N Lugenssupporting
confidence: 57%
“…For example, Jay et al have demonstrated the potential of vegetation indices in high-throughput phenotypic analyses by conducting inversion of LAI, chlorophyll, and nitrogen content in sugar beet crops using multi-source data [53]. Additionally, Lu et al have provided practical insights for the remote monitoring of jujube mite infestation by inverting jujube leaf chlorophyll content under spider mite stress using ensemble algorithms [54]. Yuzhen Wu et al used unmanned aerial vehicle hyperspectral remote sensing to assess the multi-parameter health of jujube trees and achieved R 2 values of 0.726 and a maximum of 0.853 using the RF method [55].…”
Section: Discussionmentioning
confidence: 99%
“…PSO is a population-based intelligent optimization stochastic search algorithm ( Lu et al., 2022 ). First, the initialized particle swarm is generated as a solution in the feasible space.…”
Section: Proposed Methodsmentioning
confidence: 99%